2015
DOI: 10.3390/photonics2010139
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Polarization Modulated DirectDetection Optical CDMA Systems over Turbulent FSO LinksModeled by the Gamma-Gamma Distribution

Abstract: This paper proposes a theoretical study to characterize the transmission of optical code division multiple access (CDMA) systems deploying polarization shift keying (PolSK) over a free space optical (FSO) link under the impact of atmospheric turbulence. In our analysis, a novel transceiver architecture for atmospheric OCDMA FSO systems based on polarization modulation with direct detection is proposed and discussed. A detailed analytical model for PolSK-OCDMA systems over a turbulent FSO link is provided. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…After travelling turbulent media signal suffers degraded power and distorted phase .Moreover, AWGN is added with the signal. Considering the effect of atmospheric turbulence and pointing error the output photocurrent at receiver is given by [6,15]: (2) where R is photodetectors responsivity, h is the overall channel state, and n(t) is the Gaussian distributed noise at the output of receiver with zero mean and variance , which includes shot noise and thermal noise.…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…After travelling turbulent media signal suffers degraded power and distorted phase .Moreover, AWGN is added with the signal. Considering the effect of atmospheric turbulence and pointing error the output photocurrent at receiver is given by [6,15]: (2) where R is photodetectors responsivity, h is the overall channel state, and n(t) is the Gaussian distributed noise at the output of receiver with zero mean and variance , which includes shot noise and thermal noise.…”
Section: System Modelmentioning
confidence: 99%
“…The main challenges in atmospheric channel are turbulence, pointing jitter, scattering, absorption and attenuation due to rain, fog, cloud and snow etc. These phenomena can cause power loss in received signal [1][2][3][4]. Performance improvement in terms of bandwidth and power is done by different modulation scheme due to safety regulation of transmitted power and its cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its features and usefulness it is being used in many ways especially in access and core networks. It is now widely accepted that optical wireless technology can prove to be viable alternative to the radio and microwave [15][16][17][18][19][20]. Many encoding schemes are used in OCDMA (Optical Code Division Multiple Access Network) but SAC (Spectral Amplitude Codes) is widely used as it is considered an effective arrangement to eliminate dominant noise called MAI (Multi Access Interference [21].…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the performance of radio-over-FSO (RoFSO) systems carrying OCDMA signals has been investigated within MAInoise in the presence of turbulence. The potential for combining OCDMA and the polarization modulation scheme to increase the FSO link performance has been thoroughly discussed in our previous work [14]. Moreover, to cover the shortage of directly-detected FSO systems in overcoming the impact of atmospheric turbulence, the use of heterodyne detection as a countermeasure for the turbulence mitigation has been reported in [15,16]; it has been demonstrated that heterodyne detection can offer a better background noise rejection and increased detector sensitivity compared to direct detection.…”
Section: Introductionmentioning
confidence: 99%